Front Cover: Amphiphilic Iminosugar Pharmacological Chaperones towards β‐Glucocerebrosidase: Self‐Assembly and Biological Activity (Eur. J. Org. Chem. 11/2023). Issue 11 (6th February 2023) - Vanni, Costanza; Cardona, Francesca; Clemente, Francesca; Morrone, Amelia; Raudino, Martina; Ambrosi, Moira; Lo Nostro, Pierandrea; Matassini, Camilla
Abstract : The Front Cover shows a picture of a Ramen bowl, the famous Japanese noodle soup, that allegorically sketches the combination of the different aggregation states of the amphiphilic GCase pharmacological chaperone, object of our study. The slices of meat depict the solid state, while the boiled egg represents the micellar aggregates in solution (above the cmc). The noodles in the soup represent the misfolded GCase enzyme, which is stabilized by our compound as a monomer in the nM concentration range and symbolized by the spoon. Cover picture created by the skill of Tessa Biondi. More information can be found in the Research Article by P. Lo Nostro, C. Matassini et al .